2019
DOI: 10.1111/liv.14102
|View full text |Cite
|
Sign up to set email alerts
|

Signalling networks in cholangiocarcinoma: Molecular pathogenesis, targeted therapies and drug resistance

Abstract: Cholangiocarcinoma (CCA) is a deadly disease. While surgery may attain cure in a minor fraction of cases, therapeutic options in either the adjuvant or advanced setting are limited. The possibility of advancing the efficacy of therapeutic approaches to CCA relies on understanding its molecular pathogenesis and developing rational therapies aimed at interfering with oncogenic signalling networks that drive and sustain cholangiocarcinogenesis. These efforts are complicated by the intricate biology of CCA, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 212 publications
(451 reference statements)
1
56
0
4
Order By: Relevance
“…Promising new agents in early clinical development for the treatment of CCA include compounds that target the JAK/STAT pathway, the Wnt/β-catenin signaling and the Hedgehog signaling (HH) pathways. JAK/STAT pathway activation is directly involved in several cellular process characteristics of cancer cells, including cell growth, proliferation, and apoptosis [80][81][82].…”
Section: Other Target Agents In Early Clinical Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Promising new agents in early clinical development for the treatment of CCA include compounds that target the JAK/STAT pathway, the Wnt/β-catenin signaling and the Hedgehog signaling (HH) pathways. JAK/STAT pathway activation is directly involved in several cellular process characteristics of cancer cells, including cell growth, proliferation, and apoptosis [80][81][82].…”
Section: Other Target Agents In Early Clinical Developmentmentioning
confidence: 99%
“…Multiple WNT pathway inhibitors are currently under clinical development (see Table 2). The activation of the hedgehog pathway results in chronic hepatic inflammation, fibrosis, cholangiopathies and in the development of CCA [80,83]. In cancer specimens of CCA, the expression of Hedgehog pathway components have been associated with disease stage and prognosis [85].…”
Section: Other Target Agents In Early Clinical Developmentmentioning
confidence: 99%
“…To determine whether DLL4, VEGFA, and MMP13 are NOTCH direct transcriptional targets, we performed an in silico prediction of the binding sites for RPBJ, the transcriptional co-activator of NOTCH [7], on DLL4, VEGFA, and MMP13 gene promoters using the EPDnew database [21]. Noticeably, we identified several putative binding sites for RPBJ on DLL4, VEGFA and MMP13 gene promoter regions (P < 0.01; Supplementary Fig.…”
Section: Validation Of Dll4 Vegfa and Mmp13 Genes As Direct Notch Tmentioning
confidence: 99%
“…Both receptors and ligands are cell surface transmembrane proteins, and therefore, Notch activation is initiated by direct cell-cell interactions. Once generated, NICD enters the cell nucleus and binds RBPJ, which acts as a transcriptional co-activator, by inducing important effects on cell fate, reprogramming, and growth [7]. Thus, it is not surprising that the gamma-secretase inhibitor (GSI) LY3039478, orally administered, is currently under investigation in clinical trials for different gastrointestinal advanced malignancies (https://clinicaltrials.…”
Section: Introductionmentioning
confidence: 99%
“…1 A range of perturbed signaling pathways and genomic alterations was found to be associated with late-stage cholangiocarcinoma, but there is still limited knowledge about how such pathways and mutations evolve throughout tumorigenesis. [2][3][4][5][6][7][8] Moreover, our understanding of this process is further complicated by the observation that iCCA can arise from several cell types, namely cholangiocytes, hepatocytes, progenitor cells and peribiliary glands. [9][10][11][12][13][14][15][16] Histopathological studies identified two subtypes of iCCA in humans.…”
Section: Introductionmentioning
confidence: 99%